(untitled) (Journal of Contemporary Studies, 2018)
Abstract Changes in Russia’s foreign policy demonstrate Moscow’s effort to integrate itself into the Asia Pacific region. This research analyzes the international, regional and domestics factors responsible for change in Moscow’s foreign policy and studies its likely implications for Pakistan. At the international level, this change is an attempt to balance against the American led unipolar world. At the regional level, Russia wants to curb the increasing American influence and is thus actively participating in regional affairs and strengthening ties with the regional states. Increasing engagement with South Asian nations as a part of this strategy would not only affect the regional security complex, but will also impact Pakistan. Pak-Russia emerging entente will provide multi-faceted opportunities to Pakistan in the fields of trade, energy and defense. Pakistan needs to diversify its foreign policy by opening up for Russian engagement based on mutual interests and reciprocity.